2021
DOI: 10.1186/s12903-021-01936-y
|View full text |Cite
|
Sign up to set email alerts
|

Guided endodontics: accuracy of access cavity preparation and discrimination of angular and linear deviation on canal accessing ability—an ex vivo study

Abstract: Background Guided endodontics technique has been introduced for years, but the accuracy in different types of teeth has yet to be assessed. The aim of this study is to evaluate the accuracy of three dimensional (3D)-printed endodontic guides for access cavity preparation in different types of teeth, and to evaluate the predictive ability of angular and linear deviation on canal accessibility ex vivo. Method Eighty-four extracted human teeth were mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 38 publications
0
15
1
Order By: Relevance
“…This can explain the slightly higher deviation values obtained apically. The average angular deviation was below the range reported by other authors [13,14,28].…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…This can explain the slightly higher deviation values obtained apically. The average angular deviation was below the range reported by other authors [13,14,28].…”
Section: Discussioncontrasting
confidence: 76%
“…The authors reported achieving minimally invasive access up to the middle of the root; however, no data was available regarding its accuracy. On the other hand, the accuracy of conventional guides used for guided endodontics has been assessed in several studies, showing mean apical deviation values smaller than 0.5 mm [13,14,[26][27][28] with a mean angular deviation between 1.59 • and 1.81 • [13,14]. Although it is difficult to compare the present study with other studies due to differences in the protocol and heterogeneous measuring methods, the deviation measurements obtained with a sleeveless guide do not seem to differ substantially from those of conventional guides.…”
Section: Discussionmentioning
confidence: 99%
“…[11] Subsequently a template is fabricated using 3D printing. [12] (Fig- 1) A template known as an endodontic guide is created to direct drills into pre-planned sites for localizing and exploring root canal orifices or for trephining bone and resealing root ends. These are used exclusively in Static Guided Endodontics.…”
Section: Tracementioning
confidence: 99%
“…3D printing helps in printing of customized endodontic guides. [14] The commercially available burs and drills include Straumann drill, SS White Endo bur, munce bur [12] . They are between 25 and 35 mm long to integrate the sleeve's length, and between 1.2 and 1.5 mm wide.…”
Section: Tracementioning
confidence: 99%
“…Su et al in their ex vivo study, also found very low linear deviation in all groups (anteriors, premolars, and molars); however, they found that the apical position had more deviation than the coronal (0.46 mm. vs. 0.13 mm); nonetheless, al canals were accessible and no root canal perforation was observed [22]. This review included one observational study by Buchgreitz et al that found that guided endodontic access can be precise irrespective of sex, age, tooth number, degree of obliteration, and previous attempts to find and negotiate the root canal in single-rooted teeth [18].…”
Section: Guided Endodontic Accessmentioning
confidence: 99%